Reinvigorating Unicorn Startup Employee Productivity Following Mass Layoffs - Rachma Dania, Rizki Firdausi; Gulabdin, Shaierah (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The transition period from the pandemic back to normal and the global recession triggered many employee layoffs, especially in unicorn startup companies. This mass layoff also had an impact on the remaining employees. This research wants to analyze how to maintain the performance of remaining employees when viewed from the influence of work stress, communication and job satisfaction. The sample is company employees in Jakarta, and the sample size is 200 people. The Jakarta location was chosen because most unicorn startup companies are in this city. The research sample was selected using a purposive sampling technique. The quantitative data processing method is carried out using the survey method. The data is processed using the Lisrel application. Unicorn startup employee, Employee Perfomance, Job satisfaction, Work stress, Communication